Effects of heavy resistance training on strength and power in upper extremities in wheelchair athletes - Turbanski, S.; Schmidtbleicher, D. (The Journal of Strength and Conditioning Research, 2010)
Little is known about strength training in subjects with spinal cord injury (SCI), especially in athletes performing competitive sports. Sixteen male subjects participated in this study-8 with SCI and 8 healthy physical education students (control subjects). The 8-week program consisted of heavy-resistance exercise performed twice per week with 10 to 12 repetitions in 5 sets. Subjects' performances were tested in static and in dynamic conditions concerning several strength and power parameters. Furthermore, we tested 10-m sprinting performance in wheelchair athletes. Overall, wheelchair athletes and control subjects achieved similar results; in almost all parameters both groups improved considerably in post-testing. Regarding percentages in most strength and power parameters, wheelchair athletes showed a tendency to benefit more from the strength training performed in the present study. Using analyses of group differences, however, only the comparison of effects on rate of force development (p = 0.010) resulted in a significant higher improvement for wheelchair athletes. In contrast to previous assumptions about minor adaptation capacities to training exercises in patients with SCI, our study proved clear effects of strength training. In conclusion, we suggest that heavy resistance training should be of increasing importance in wheelchair sports.